A Five-Component Customer Commitment Model: Implications for Repurchase Intentions in Goods and Services Industries. (November 2015) - Keiningham, Timothy L.; Frennea, Carly M.; Aksoy, Lerzan; Buoye, Alexander; Mittal, Vikas
Empirical studies in marketing conceptualize commitment as a three-component construct comprised of affective, normative, and calculative commitment. We develop and empirically test a five-component typology of consumer commitment— affective, normative, economic, forced, and habitual commitment. The broadened conceptualization of commitment is tested using qualitative and quantitative studies with data from 9, 000 consumers and 10 countries. The broadened five-component commitment model demonstrates high levels of reliability, convergent and discriminant validity, and stability, as well as unique associations with repurchase intentions. Managerially, it provides a roadmap for optimizing commitment: while forced commitment should be minimized, economic and habitual commitment should be enhanced. These prescriptions vary for goods and services. Namely, affective, normative, and habitual commitment exhibit stronger positive effects on repurchase intentions for goods than for services; the opposite pattern is found for economic commitment. By showing how managers should optimize specific commitment dimensions rather than simply maximize overall commitment, while accounting for contextual factors such as differences between goods and services, our results provide an actionable strategic blueprint for firms' customer commitment strategy.